Multiple HPV-Induced Squamous Cell Carcinomas on the Fingers of a Patient with Systemic Lupus Erythematosus: A Case and Review - Georgios Nikolakis; Ioannis Karagiannidis; Vasiliki A. Zampeli; Andreas Altenburg; Martina Brunner; Christos C. Zouboulis (Karger Publishers, 2015)
Human papilloma virus (HPV) infection is documented to be involved in the development of epithelial malignancies, mostly in cervical cancer. Systemic lupus erythematosus (SLE) patients have an increased prevalence of such an infection. We report the case of a 55-year-old female SLE patient who developed multiple in situ squamous cell carcinomas on her fingers, after chronic HPV infection. HPV-33 DNA was isolated from the lesions. The purpose of this case presentation is to raise awareness about HPV-induced malignancies for this high-risk group and propose an early HPV vaccination to efficiently prevent such comorbidities.